The value of biomarkers in the diagnosis and prognostic analysis of IgA nephropathy - Lu Min; Li Gui-sen (Linchuang shenzangbing zazhi)
Immunoglobulin A nephropathy （IgAN） is the most common primary glomerulonephritis worldwide and the main cause of chronic kidney disease and renal failure worldwide. Its etiology and pathogenesis are still unknown， and the most reliable method for clinical diagnosis of this disease is kidney biopsy. Due to the invasive risk， renal biopsy is not usually used to monitor the clinical course or prognostic response. Therefore， it is urgent to find accurate and reliable non-invasive biomarkers for the diagnosis and prognosis of IgA nephropathy. In this paper， we reviewed the classification and current research status of newly discovered biomarkers in IgA nephropathy in recent years， including the application of the latest omics techniques in the diagnosis and prognosis of IgAN.